The legal country in a life of modern society (philosophical analysis) (Journal of Philosophy Culture and Political Science, 2018)
The main goal of the research is to reveal philosophically the essence and specificity of the legalculture in a life of modern society.In accordance with this goal, the following problems are posed and solved in the study:– to conduct a systematic analysis of the material accumulated in theory and social practice relevantto the topic;– to reveal the essence and specificity of legal culture as a significant spiritual and social phenomenon;– to disclose the substantive basis of the notion of value orientations;– to present the youth’s value orientations, innovations in value orientations, taking place in theconditions of social transformations of Kazakhstan in the modern stage.Theoretical and methodological basis of the research are the works of the classics of the world anddomestic philosophy and theory of law. The methodological basis is the program documents of development– independent Kazakhstan on the path of building a legal state and civil society, in which the factorof legal culture occupies a significant and necessary place. The strategic guidelines of the right-culturaltransformations are set forth in the works of the President of the Republic of Kazakhstan – N.A. Nazarbayev.The task is to understand two immutable rules. First, no modernization can take place withoutpreserving the national culture. Secondly, in order to move forward, we must abandon those elementsof the past that do not allow the nation to develop (Nazarbayev, 2017).An important theoretical basis of the work are the works of modern philosophers, culturologists,jurists, political scientists, sociologists and educators.The initial methodological principles of problem analysis are: the unity of induction and deduction,empirical and theoretical, historical and logical, abstract and concrete, comparative analysis, etc.The scientific and practical importance of the research is determined by the fact that its results canbe used in the development of courses in philosophy, political science, sociology and other humanitariandisciplines, they can prove useful in the work of the media, internal policy departments and otherstate structures in shaping public opinion, when studying the trends in the development of mass consciousness.Key words: youth, value orientations, society of transitional type, law culture, socialization, development.